EVALUASI KEPUASAN SISWA PADA APLIKASI ADOBE PHOTOSHOP MENGGUNAKAN METODE END USER COMPUTING SATISFACTION - Setiyanto, Sigit; Yasin, Ilham Fatah; Nafiuddin, Ahmad Muhandis (Universitas Aisyiyah Surakarta, 2023)
This research is an activity to determine student satisfaction with Adobe Photoshop software using the end-user computing satisfaction (EUCS) method. This research aims to obtain application evaluation results regarding the level of student satisfaction as a user and recommendations for technical improvements to the Adobe Photoshop application into a better application. At the stage of the research analysis process, the quantitative descriptive analysis method was used. The results obtained from the student satisfaction survey in this study reached a satisfaction level of 66%. The results of the analysis are calculated from the analysis with attribute values, content value 73%, accuracy value 64%, format value 72%, ease of use value 54%, and timeline value 65%. The results of this survey in the end-user computing satisfaction (EUCS) assessment category, Adobe Photoshop software users expressed satisfaction. Adobe Photoshop software needs to improve several aspects to make it better, especially the editing tool selection feature that can make it easier to choose to select objects in detail and detail